Inhibition of CD95/CD95L (FAS/FASLG) signaling with APG101 prevents invasion and enhances radiation therapy for glioblastoma - Blaes, Jonas; Sahm, Felix; Wick, Antje; Deimling, Andreas von; Haberkorn, Uwe; Abdollahi, Amir; Debus, Jürgen; Bendszus, Martin; Platten, Michael; Wick, Wolfgang; Lemke, Dieter (Molecular cancer research, 2018)
CD95 (Fas/APO-1), a death receptor family member, activity has been linked to tumorigenicity in multiple cancers, including glioblastoma multiforme (GBM). A phase II clinical trial on relapsed glioblastoma patients demonstrated that targeted inhibition of CD95 signaling via the CD95 ligand (CD95L) binding and neutralizing Fc-fusion protein APG101 (asunercept) prolonged patient survival. Although CD95 signaling may be relevant for multiple aspects of tumor growth, the mechanism of action of APG101 in glioblastoma is not clear. APG101 action was examined by in vitro proliferation, apoptosis, and invasion assays with human and murine glioma and human microglial cells, as well as in vivo therapy studies with orthotopic gliomas and clinical data. APG101 inhibits CD95L-mediated invasion of glioma cells. APG101 treatment was effective in glioma-bearing mice, independently of the presence or absence of CD4 and CD8 T lymphocytes, which should be sensitive to CD95L. Combined with radiotherapy, APG101 demonstrated a reduction of tumor growth, fewer tumor satellites, reduced activity of matrix metalloproteinases (MMP) as well as prolonged survival of tumor-bearing mice compared with radiotherapy alone. Inhibiting rather than inducing CD95 activity is a break-of-paradigm therapeutic approach for malignant gliomas. Evidence, both in vitro and in vivo, is provided that CD95L-binding fusion protein treatment enhanced the efficacy of radiotherapy and reduced unwanted proinfiltrative effects by reducing metalloproteinase activity by directly affecting the tumor cells. - Implications: APG101 (asunercept) successfully used in a controlled phase II glioblastoma trial (NCT01071837) acts anti-invasively by inhibiting matrix metalloproteinase signaling, resulting in additive effects together with radiotherapy and helping to further develop a treatment for this devastating disease. Mol Cancer Res; 16(5); 767–76. ©2018 AACR.
Gesehen am 11.09.2019